Relationship Between Education Level, Age and Knowledge of Pregnant Women with Antenatal Care Status - Fegita, Primadella; Hikmah, Miftahul; Malik, Rifkind (CV. AKBAR PUTRA MANDIRI, 2022)
Background: Maternal mortality in Indonesia was still quite high. To reduce the mortality rate of the government made a health care program for pregnant women, namely antenatal care services (ANC). Education, knowledge and age of mothers were one of the determinants of maternal death. The purpose of this study was to determine the relationship of formal education levels, maternal age and level of knowledge with health to ANC. Method: Observational analytic research type with a cross-sectional approach, using primary data, namely quizerer and secondary book data KIA. Data were analyzed univariate and bivariate using Spearman Rho test. Results: Univariate analysis, pregnant women with a higher education level of 7 people (21.9%), while 8 people (25.0%), 17 people (53.1%); Pregnant women with the same high and low knowledge level, 50%; Mother's age <20 years and> 35 years 10 people (31.3%) and mothers age 20-35 years 22 people (68.8%); Pregnant women with a complete ANC status of 15 people (46.9%), and 17 people were incomplete (53.1%); Spearman Rho Bivariat Test, the relationship of the level of formal education and the level of maternal knowledge with ANC P <0.05, while maternal age relations with ANC P> 0.05. Conclusion: The majority of pregnant women with low educated with the age range of 20-35 years. There was a significant and direct relationship between the level of education and the level of knowledge with ANC status.